Soft-switching PWM full-bridge converters : topologies, control, and design - Ruan, Xinbo (Wiley/Science Press, 2014)
Soft-switching PWM full-bridge converters have been widely used in medium-to-high power dc-dc conversions for topological simplicity, easy control and high efficiency. Early works on soft-switching PWM full-bridge converter by many researchers included various topologies and modulation strategies. However, these works were scattered, and the relationship among these topologies and modulation strategies had not been revealed. This book intends to describe systematically the soft-switching techniques for pulse-width modulation (PWM) full-bridge converters, including the topologies, control a.